2011
DOI: 10.1152/ajpgi.00466.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine in GI

Abstract: Recent advances in nanotechnology offer new hope for disease detection, prevention, and treatment. Nanomedicine is a rapidly evolving field wherein targeted therapeutic approaches using nanotechnology based on the pathophysiology of gastrointestinal diseases are being developed. Nanoparticle vectors capable of delivering drugs specifically and exclusively to regions of the gastrointestinal tract affected by disease for a prolonged period of time are likely to significantly reduce the side effects of existing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 109 publications
0
51
0
Order By: Relevance
“…8 Nanoparticulate delivery systems offer great promise and advantages in the administration of drugs also via the oral route because they are able to carry sufficient amounts of drugs that could be released at specific sites, at a specific pH value, be resistant toward digestive enzymes, and control the release of encapsulated or associated drug. 9,10 Due to these advantages, nanoparticle formulation approaches have proven to be very useful for drug delivery applications, including oral formulations. [11][12][13] Moreover, employing nanomedical concepts such as cellular targeting and intracellular drug release in oral delivery further offers the possibility of efficient and specific delivery to cells within the intestinal epithelium and thereby to specific regions of the gastrointestinal (GI) tract, offering more efficacious treatment possibilities for intestinal diseases such as colon cancer and inflammatory bowel diseases, not attainable via systemic drug delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Nanoparticulate delivery systems offer great promise and advantages in the administration of drugs also via the oral route because they are able to carry sufficient amounts of drugs that could be released at specific sites, at a specific pH value, be resistant toward digestive enzymes, and control the release of encapsulated or associated drug. 9,10 Due to these advantages, nanoparticle formulation approaches have proven to be very useful for drug delivery applications, including oral formulations. [11][12][13] Moreover, employing nanomedical concepts such as cellular targeting and intracellular drug release in oral delivery further offers the possibility of efficient and specific delivery to cells within the intestinal epithelium and thereby to specific regions of the gastrointestinal (GI) tract, offering more efficacious treatment possibilities for intestinal diseases such as colon cancer and inflammatory bowel diseases, not attainable via systemic drug delivery.…”
mentioning
confidence: 99%
“…[11][12][13] Moreover, employing nanomedical concepts such as cellular targeting and intracellular drug release in oral delivery further offers the possibility of efficient and specific delivery to cells within the intestinal epithelium and thereby to specific regions of the gastrointestinal (GI) tract, offering more efficacious treatment possibilities for intestinal diseases such as colon cancer and inflammatory bowel diseases, not attainable via systemic drug delivery. 9,10 In oral formulations, amorphous silicon dioxide (SiO 2 ) or silica, has been used as a pharmaceutical excipient for .50 years and is classified by the US Food and Drug Administration as generally regarded as safe.…”
mentioning
confidence: 99%
“…The targeting of drug delivery to the inflamed colon can be divided into three levels: targeting the colon (organ level), targeting inflamed colon sites (tissue level), and targeting specific cells (cell level) [16]. Most of the current oral formulations for IBD therapy, which include pellets, capsules, and tablets, are based on pH-, pressure-, or bacteria-responsive mechanisms [17], and can only perform organ-level targeting. NPs, in contrast, have the potential to accumulate in inflamed colon tissues passively, and studies have shown that reactive oxygen species (ROS)-sensitive formulations can induce active targeted drug delivery at the tissue level [18].…”
Section: Oral Administrationmentioning
confidence: 99%
“…34 Physiologic pH in the human body ranges from ~3 in the stomach to ~5-6 in the small intestine and 7 in the colon. 35 We therefore tested the pH stability of our NPs by adjusting the pH to 3, 5, and 7 with hydrochloric acid. The PEGylated particles did not change in size regardless of pH; however, the OH terminated did increase from 77 to 110 nm (Figure 2A).…”
mentioning
confidence: 99%